2009
DOI: 10.1016/j.molbiopara.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomphalaria glabrata peroxiredoxin: Effect of Schistosoma mansoni infection on differential gene regulation

Abstract: To identify gene(s) that may be associated with resistance/susceptibility in the intermediate snail host Biomphalaria glabrata to Schistosoma mansoni infection, a snail albumen gland cDNA library was differentially screened and a partial cDNA encoding an antioxidant enzyme thioredoxin peroxidase (Tpx), or peroxiredoxin (Prx), was identified. The 753 bp full-length, single-copy, constitutively expressed gene now referred to as BgPrx4 was later isolated. BgPrx4 is a 2-Cys peroxiredoxin containing the conserved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…The findings for prx1 and infPhox echoe a similar change reported for peroxiredoxin 4 ( prx4 ) by Knight et al (2009). Peroxiredoxins require conserved cysteines to scavenge (detoxify) hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionsupporting
confidence: 72%
“…The findings for prx1 and infPhox echoe a similar change reported for peroxiredoxin 4 ( prx4 ) by Knight et al (2009). Peroxiredoxins require conserved cysteines to scavenge (detoxify) hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionsupporting
confidence: 72%
“…In B . glabrata snails, it has been previously shown that the differential capability of host defense responses in susceptible and resistant snails could have different effects on enzyme activity due to the differences in the levels of these enzymes in each strain [31, 79, 80]. Serpin is a serine protease inhibitor that was only found expressed in plasma with an up-regulated expression profile at 24 and 48 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…The 25 μl final reaction volume contained; 200 nM of each gene specific primers for nimbus RT (Raghavan, et al, 2003) and Hsp 70 or 50 nM of the housekeeping gene, myoglobin primers (Raghavan, et al, 2003). Reactions were performed in a one-step format with the first stand cDNA synthesis and Real time PCR amplification done in a single tube in triplicate as described previously (Knight, et al, 2009). Each reaction contained a no template negative control to rule out non-specific amplification from contamination in the buffers and data was normalized using myoglobin as the reference housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%